Analysis Of Factors Related To The Incidence Of Acute Respiratory Infection In Toddlers In The Area Of Tuntungan Community Health Center, Deli Serdang Regency 2024 - Suhartina Suhartina; Santy Deasy Siregar; Sarah Oculi Zaluchu (CV. Inara, 2025)
According to the WHO (World Health Organization), acute respiratory infection (ARI) is an infectious disease of the upper or lower respiratory tract that can cause various types of diseases, from asymptomatic diseases or mild infections to severe and fatal diseases, depending on the causative pathogen, environmental factors, and host factors. Acute respiratory infection (ARI) is caused by more than 300 bacteria, viruses, and rickettsia types. The incidence, distribution, and consequences of acute respiratory infections vary based on several factors, namely environmental conditions, such as air pollution, household density, humidity, cleanliness, season and temperature; availability and effectiveness of medical care; infection prevention and control (IPC) measures to contain the spread, such as vaccines, access to health care facilities, and isolation capacity; individual factors, such as age, smoking, the ability of personal factors to transmit infection, immune status, nutritional status, previous or concurrent infections with other pathogens, and underlying medical conditions; pathogen characteristics, such as mode of transmission, transmissibility, virulence factors and microbial load (WHO, 2020). This study aims to analyze several factors related to the incidence of ARI in toddlers in the Tuntungan Health Center area, Deli Serdang Regency, in 2024. This research method uses a questionnaire containing questions to obtain primary data from respondents. The questionnaire is processed using validity, reliability, normality, and logistic regression tests. This study concludes that environmental factors, such as maternal education history, individual children, nutrition, socioeconomics, and family smoking behavior, have a relationship with the incidence of ARI in toddlers. In contrast, the results for immunization factors show no relationship with the incidence of ARI in toddlers.